Analisis Konservasi Kawasan Banjir Di Kota Bandung: Studi Kasus Kecamatan Sukasari - Dewi Pramudita Maryudi; Farzda Dwi Prahandani; Lisa Wulandari; M. Vernanda Vikry D.; Hany Nurpratiwi (Populer: Jurnal Penelitian Mahasiswa, 2023)
This research aims to analyze the conservation or solutions to flood disaster problems as a community need with a healthy environment. The research was conducted in Sukasari District, Bandung City, West Java Province, with an area of 6.27 km2. The method used in this paper is descriptive analysis and the data used is secondary data. Based on the analysis of the flood hazard map for Bandung City, the research results show that the entire area of Sukasari District is highly prone to flooding. Based on the findings, the overflow of the Cidurian, Cipamokolan, and Cibeureum rivers poses a threat of flooding in Sukasari sub-district. Green Open Spaces in Sukasari District consist of 16 location points spread across 3 sub-districts. The utilization of Green Open Spaces serves to maintain ecosystem balance and increase the availability of clean air and water catchment areas. Solutions to reduce flood disasters include reducing the level of risk, decreasing vulnerability, and enhancing community capacity.